Rock slope failure in a recently deglaciated permafrost rock wall at Piz Kesch (Eastern Swiss Alps), February 2014. Issue 3 (21st July 2016) - Phillips, Marcia; Wolter, Andrea; Lüthi, Rachel; Amann, Florian; Kenner, Robert; Bühler, Yves
Abstract: In February 2014, a rock pillar with a volume of around 150 000 m 3 collapsed at Piz Kesch in the Eastern Swiss Alps. A reconstruction of the conditions prior to the event and of the event itself is presented on the basis of different sources of data. The methods applied include photogrammetry, terrestrial laser scanning, structural geological analysis, examination of meteorological data, carbon‐14 ( 14 C) dating of organic material in permafrost ice from a tension crack and numerical modelling of likely modes of failure. Despite a complete lack of in situ measurements in the rock wall prior to the event and of direct observations during the event, the available data allow the determination of the approximate timing of the event as well as the structural predisposition, the probable mode of failure and the timescale of several millennia involved in the triggering of the failure of the rock pillar. The interdisciplinary analysis of this event contributes towards understanding the complex interaction of processes involved in large rock slope failures currently occurring in warming mountain permafrost regions. Copyright © 2016 John Wiley & Sons, Ltd.